Thermo inductive nondestructive testing method applied to CFRP. (2014) - ,; ,; ,; ,; ,; ,
Abstract : Purpose – In this paper, a thermo inductive nondestructing testing (NDT) modeling applied to carbon fiber reinforced polymer (CFRP) composite is presented. The paper aims to discuss these issues.Design/methodology/approach – A multi‐scale approach is used to calculate the electromagnetic and thermal field distribution.Findings – The temperature perturbation due to the presence of flaws can be detected at the surface of the composite by an infrared camera.Originality/value – The developed 3D thermomagnetic model can be used to study the efficiency of the thermal inductive method for different kind of flaws, inductors and frequencies.